Analisis Respon Warga Nahdiyyin Terhadap Sistem Keuangan Syariah di BMT NU Jawa Timur Cabang Utama Gapura - Saidatul Qomaria; Mawardi Mawardi (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
The purpose of this study was analyze the response of nahdiyyin residents to the islamic financial system at BMT NU eats java the main branch of gapura. The method used in this research is using descriptive qualitative method which is a field research. While the approach used in this study is the siciology of islamic law. The results of the study show that the interest factor of the nahdiyyin community who are in gapura district towards the sharia financial system at BMT NU is because the community follow the kiyai and community leaders